Pengembangan Kompetensi Guru untuk Gerak Dasar Anak Usia Dini (tgmd3) dan Pelatihan Kebugaran Jasmani - Irfan Oktavianus; Pringgo Mardesia; Maltha Kharisma; Eko Purnomo; Alex Aldha Yudi; Muhammad Fakhrur Rozi; Adiska Rani Ditya Candra (JURNAL PENGABDIAN MASYARAKAT OLAHRAGA DAN KESEHATAN (JASO), 2024)
Motor learning in preschool and school education is very important to pay attention to because it has an impact on children's growth and development, as well as their mental abilities (Komaini et al. 2021). Many challenges Indonesian children face, overweight or obesity and lack of physical activity are two major challenges. More than half (65%) of the world's population lives in countries where overweight and obesity kill many people, identified as the fourth leading risk factor for global mortality(Gallahue 1989). The problem is not limited to adults and nearly 43 million children worldwide under the age of five were overweight in 2010. It is clear we need to look critically and progressively at physical activity and motor skills development. In this service, the service will run basic physical fitness and movement programs that have been adapted to the needs of school and early childhood students in Indonesia, namely the TKJI and INDO-SKIP tests. INDO SKIP is a basic motion learning program that focuses on locomotor motion and control objects that have been proven in improving the quality of children's basic movements. Meanwhile, TKJI is an Indonesian Physical Fitness Test. The target that will be carried out this year is to be able to provide training to kindergarten schools in the region to implement basic movement learning in PAUD and Sipora Middle School, Mentawai Regency. Has collaborated with the Academic community of Padang State University to develop school teachers and Village Kindergarten Teachers. For this reason, it is important to do coaching for these teachers. After training, teachers will provide independent learning about basic movements in accordance with the curriculum that has been prepared for kindergarten students.